Musculoskeletal examination and assessment : a handbook for therapists - Nicola J. Petty; Dionne Ryder (Edinburgh : Elsevier, 2018)
Now in its fifth edition, this core textbook continues to provide a comprehensive, systematic guide to the examination and assessment of patients with neuromusculoskeletal dysfunction
Keywords: Examen neurologique Guides, manuels, etc; Health and Fitness; Handbooks and manuals